Realities that English Pre-service Teachers Encounter when Conducting Research in a Distance Bachelor’s Program - Ortiz García, William Ricardo; López Urbina, Johanna Patricia (Colombian Applied Linguistics Journal, 2024)
This paper reports the results of a qualitative case study conducted with undergraduate students from a distance learning Bachelor’s degree program in Foreign Language Education Program with an emphasis on English at a private university in Colombia. This study aimed at depicting realities encountered by pre-service teachers when conducting research in EFL, and how these realities affect their process and therefore their undergraduate research reports. This qualitative study gathered data through interviews, focus groups, observation, and document analysis. The data were analyzed using MAXQDA software. The main findings showed pre-service teachers’ difficulties in finding conducive contexts in which to carry out their research, as well as difficulties related to poor time management, inconsistencies between research subjects and curricula, and differences in research tutors’ feedback and guidance as factors that might contribute to the production of biased research in the field of English as a foreign language. In conclusion, it is necessary to review institutional higher education policies to determine a range of possibilities to divulge and contribute to the academic field as part of a curricular updating process.